INFLUENCE OF BOND RATING CHANGES ANNOUNCEMENT TO RETURN SHARE OF COMPANY (On Company Who Go Public In IDX Period 2005-2007) - Rosyati, Rosyati (Jurnal Analisis Bisnis Ekonomi, 2009)
This research aim to test return share difference between before, moment, and after bond rating announcement, test return share of company before experience across classes and after experience bond rating, test difference of company return share before experience within classes and after experience within classes, test difference of return share for go public company in IDX experience bond rating changes. Based of sample intake technique obtained sample as much 36 company, that is 26 company experience across classes and 12 company experience within classes. The hypothesis test use ANOVA, paired sample t test and independent sample t test. Result of research show that no difference between return share before, moment and after bond rating announcement. No advanced company return share before experience across classes and after experience across classes. No decreased return share between before and after bond rating announcement experience within classes. No diffrence return share between company exprience across classes bond rating and company experience within classes bond rating.